2013
DOI: 10.1002/ardp.201300087
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Biological Evaluation of 4‐Phenoxy‐6,7‐disubstituted Quinolines Possessing Semicarbazone Scaffolds as Selective c‐Met Inhibitors

Abstract: Novel quinoline derivatives bearing acyclic semicarbazones were prepared and their chemical structures as well as the relative stereochemistry were confirmed. All the synthesized compounds were evaluated for their c-Met kinase inhibitory activity and their cytotoxicity against the cell lines HT-29, MKN-45, and MDA-MB-231 in vitro. Several potent compounds were further evaluated against A549 cells. Most compounds displayed moderate to excellent activity, and the structure-activity relationship studies identifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 27 publications
(24 reference statements)
0
8
0
Order By: Relevance
“…Scheme depicts the preparation of compounds 20–29 . The key intermediates of 4‐(2‐fluorophenoxy)quinolones 12a–e were synthesized through an eight‐step reaction starting from commercially available 1‐(4‐hydroxy‐3‐methoxyphenyl)‐ethanone which has been illustrated in detail in our previous study .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Scheme depicts the preparation of compounds 20–29 . The key intermediates of 4‐(2‐fluorophenoxy)quinolones 12a–e were synthesized through an eight‐step reaction starting from commercially available 1‐(4‐hydroxy‐3‐methoxyphenyl)‐ethanone which has been illustrated in detail in our previous study .…”
Section: Resultsmentioning
confidence: 99%
“…The c‐Met inhibitors undergoing clinical trials or launched suggested that quinoline pharmacophores were essential for furnishing hydrogen bonds with the backbone of c‐Met kinase, and the aryl fragment (moiety B) probably generated hydrophobic binds. Importantly, there should be two structural characteristics on the linkage (moiety C) between moiety A and B, one is 5‐atoms regulation and the other is possessing hydrogen‐bond donors or acceptors simultaneously . In our previous studies, a variety of pharmacodynamics skeletons were introduced as the linker, which resulted in various derivatives 6–10 (Fig.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As shown in Scheme , the key intermediate 3‐fluoro‐4‐(6‐methoxy‐7‐((3‐substituted aminopropyl)oxy)quinolin‐4‐yloxy)aniline ( 20a – d ) was prepared from acetovanillone which was claimed in detail in our previous study .…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, a lot of new small molecule inhibitors have emerged, such as Foretinib, BMS-777607, SGX-523 and Cabozatinib (Logan, 2013;Sharma et al, 2013;Buchanan et al, 2009;Karras et al, 2013), some of which are at a clinical trial stage and some have even been launched (Albrecht et al, 2008). , N 1 -(3-fluoro-4-{6-methoxy-7-[3-(4-methylpiperidin-1-yl) propoxy] quinolin-4-yloxy}phenyl)-N4-(2,4-difulurobenzylidene) semicarbazided, is a selective quinoline-based multitarget c-Met kinase inhibitor (Qi et al, 2013a(Qi et al, , 2013b) that exhibits significant cytotoxicity against a number of cancer cell lines in vitro, such as HT-29, MKN-45, MDA-MB-231 and A549 cells (Qi et al, 2013a(Qi et al, , 2013b. Compared with Foretinib, it increased by 48.4-, 3.6-, 2.1-and 3.3-fold the cytotoxic activity against U87MG, NCI-H460, A549 and HT-29 cell lines, respectively (Qi et al, 2013a(Qi et al, , 2013b.…”
mentioning
confidence: 99%